Influence of bio-filter configurations on hydraulic aspects while enhancing the sustainable self-purification of agricultural drainage water - Alrowais, Raid; Jatwary, Ashraf; Bindzarova Gergelova, Marcela; Akrami, Mohammad; Alwushayh, Bandar; Elkamhawy, Elsayed (Frontiers in Environmental Science, 2025)
As global climate change exacerbates water scarcity, recycling agricultural drainage water is emerging as a promising solution in water resources-limited regions. This research investigated the hydraulic impact of using gravel bio-filters in contaminated water-courses, focusing on submerged bioreactors as a sustainable engineering solution. This study assessed the hydraulic impacts of installing these bioreactors in polluted waterways using three-dimensional numerical models based on computational fluid dynamics. Results indicated that relative heading-up will increase with the Froude number, demonstrating a direct relationship between flow velocity and heading-up. Altering the shape of bio-filter inlet is predicted to significantly influence heading-up values, with triangular shapes showing the lowest heading-up values compared to basic, rounded, or sloped upstream U.S face shapes. Relative heading-up values will increase by 10.32%, 10.44%, 24.67%, and 31.86% when changing the bio-filter inlet shape from triangular to sloped U.S. face with respect to horizontal and vertical direction, rounded, and basic bio-filter, respectively. Additionally, the number and orientation of shapes in the bio-filter inlet impact relative heading-up, with varying effects predicted based on the inclination angle. These findings provide valuable guidance for mitigating hydraulic impacts and optimizing the design and operation of bioreactors in water resource management, promoting sustainable water purification approaches in contaminated watercourses and conserving surrounding environments.